2011
DOI: 10.1162/jocn_a_00003
|View full text |Cite
|
Sign up to set email alerts
|

Trait Anxiety Modulates the Neural Efficiency of Inhibitory Control

Abstract: Abstract■ An impairment of attentional control in the face of threat-related distracters is well established for high-anxious individuals. Beyond that, it has been hypothesized that high trait anxiety more generally impairs the neural efficiency of cognitive processes requiring attentional control-even in the absence of threat-related stimuli. Here, we use fMRI to show that trait anxiety indeed modulates brain activation and functional connectivities between task-relevant brain regions in an affectively neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

23
126
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(153 citation statements)
references
References 87 publications
(136 reference statements)
23
126
4
Order By: Relevance
“…Studies have shown that anticipatory worry correlates with task-elicited activity and glucose consumption in dorsolateral prefrontal cortex (Tillfors, Furmark, Marteinsdottir, & Fredrikson, 2002). Furthermore, task fMRI studies point toward aberrant functional interactions between prefrontal control regions and subcortical areas in highly anxious participants (Basten et al, 2011;Bishop, Duncan, Brett, & Lawrence, 2004), and evidence from structural tractography suggests that individual differences in prefrontal-subcortical white matter projections represents a neurostructural correlate of anxiety . Although the insular-opercular network has been most dominantly implicated in anxiety (Vaidya & Gordon, 2013), other resting-state networks such as the frontoparietal control network comprising the dorsolateral prefrontal cortex, medial anterior cingulate, and the intraparietal lobule (Dosenbach et al, 2008) and the default-mode network have also been hypothesized to play a relevant role (Sylvester et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown that anticipatory worry correlates with task-elicited activity and glucose consumption in dorsolateral prefrontal cortex (Tillfors, Furmark, Marteinsdottir, & Fredrikson, 2002). Furthermore, task fMRI studies point toward aberrant functional interactions between prefrontal control regions and subcortical areas in highly anxious participants (Basten et al, 2011;Bishop, Duncan, Brett, & Lawrence, 2004), and evidence from structural tractography suggests that individual differences in prefrontal-subcortical white matter projections represents a neurostructural correlate of anxiety . Although the insular-opercular network has been most dominantly implicated in anxiety (Vaidya & Gordon, 2013), other resting-state networks such as the frontoparietal control network comprising the dorsolateral prefrontal cortex, medial anterior cingulate, and the intraparietal lobule (Dosenbach et al, 2008) and the default-mode network have also been hypothesized to play a relevant role (Sylvester et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This might be relevant for the specification of neurobehavioral theories: A prominent psychological theory on attentional control, for instance, discusses the relevance of trait anxiety for processing efficiency, which refers to the relationship between the efforts or resources invested during task performance and the quality of task performance (Eysenck, Derakshan, Santos, & Calvo, 2007). Predictions of this theoretic account have been successfully tested using task fMRI (Basten et al, 2011), yet it remains unclear why trait anxiety would affect processing efficiency. One possible account would be suboptimal information exchange capability between relevant brain areas, which might be reflected in network efficiency as indexed by path lengths in relevant functional networks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been recently argued that trait anxiety is related to deficiencies in the executive control attentional network, while state anxiety is associated with hyperactivity of the alerting and orienting networks (Pacheco-Unguetti, Acosta, Callejas, & Lupianez, 2010). Consistent with ACT, neuroimaging studies demonstrated that high-anxious individuals had to invest more cognitive (compensatory) efforts in task performance which manifested itself as an increased task-related activation of the prefrontal cortex (PFC) (Ansari & Derakshan, 2011;Basten, Stelzel, & Fiebach, 2011;Eisenberger, Lieberman, & Satpute, 2005). At the same time, the reduced sustained activity of the PFC in high-anxious individuals was reported.…”
mentioning
confidence: 99%